Effects of vanadium carbide on sintered WC-10%Co produced by micro-powder injection molding - Wong, Yee Ning; Norhamidi Muhamad,; Abu Bakar Sulong,; Abdolali Fayyaz,; Muhammad Rafi Raza, (Universiti Kebangsaan Malaysia, 2015)
Ultrafine, cemented tungsten carbide (WC) possesses exceptional hardness, wear resistance and high strength in various applications. In this study, WC was produced through micro powder injection molding (μPIM), which is also applicable for metals and ceramics in producing complex parts with high-dimensional accuracy. Different inhibitors, such as VC, Cr2C3, NbC, or TaC, were added to improve the mechanical properties of WC and control its grain growth. The effects of a grain growth inhibitor were investigated by adding VC in WC–10%Co–nVC, where n = 0 to 1.2 wt. %. The mechanical properties of the sintered part, such as hardness and flexural strength, were determined. The morphology and elemental distribution of the samples were studied by field emission scanning electron microscopy and energy-dispersive X-ray spectroscopy. X-ray diffraction was employed to study the phases of the obtained samples. The results showed that the sample with 0.4 wt. % VC (optimal amount) sintered at 1410°C exhibited the highest theoretical density, hardness and flexural strength of 95.2%, 1973±31 HV and 2586±172 MPa, respectively. The average grain size measured was 519±27 nm. VC acted as a grain growth inhibitor during sintering, thereby improving the mechanical properties.